Video Gaming as Practical Accomplishment: Ethnomethodology, Conversation Analysis, and Play. (30th November 2016) - Reeves, Stuart; Greiffenhagen, Christian; Laurier, Eric
Abstract: Accounts of video game play developed from an ethnomethodological and conversation analytic (EMCA) perspective remain relatively scarce. This study collects together an emerging, if scattered, body of research which focuses on the material, practical "work" of video game players. The study offers an example‐driven explication of an EMCA perspective on video game play phenomena. The materials are arranged as a "tactical zoom." We start very much "outside" the game, beginning with a wide view of how massive‐multiplayer online games are played within dedicated gaming spaces; here, we find multiple players, machines, and many different sorts of activities going on (besides playing the game). Still remaining somewhat distanced from the play of the game itself, we then take a closer look at the players themselves by examining a notionally simpler setting involving pairs taking part in a football game at a games console. As we draw closer to the technical details of play, we narrow our focus further still to examine a player and spectator situated "at the screen" but jointly analyzing play as the player competes in an online first‐person shooter. Finally, we go "inside" the game entirely and look at the conduct of avatars on‐screen via screen recordings of a massively multiplayer online game. Having worked through specific examples, we provide an elaboration of a selection of core topics of ethnomethodology and conversation analysis that is used to situate some of the unstated orientations in the presentation of data fragments. In this way, recurrent issues raised in the fragments are shown as coherent, interconnected phenomena. In closing, we suggest caution regarding the way game play phenomena have been analyzed in this study, while remarking on challenges present for the development of further EMCA‐oriented research on video game play. Abstract : Like Cognitive Science, Ethnomethodological and Conversation Analytics (EMCA) focuses on human activities that occur during game play. In Newell's terms, the goals of EMCA and CogSci focus on different timescales of human action and, thereby, ask different but complementary questions. The paper is written to demonstrate the utility of the EMCA approach and to emphasize the contrast between the questions asked by CogSci and EMCA.